Recent progress in the asymmetric Mannich reaction - Xiao-Hua, Cai; Hui, Guo; Bing, Xie (European Journal of Chemistry, 2012)
The asymmetric Mannich reaction is one of the most useful carbon-carbon bond forming reactions for the synthesis of chiral molecules containing nitrogen. The resulting β-amino carbonyl compounds are valuable synthons in the preparation of many natural products with useful biological properties. In recent years, asymmetric Mannich processes have increasingly been reported and used in a rapidly growing number of applications. This review provides an overview of the recent history of the applications of various catalytic systems in asymmetric Mannich reaction, including metal-based asymmetric organocatalysis, asymmetric organocatalysis, other chiral catalysis and no chiral catalysis systems.